David and Goliath in the North : a study of how the local industries in Helgeland can become more competitive in the Norwegian oilfield service industry - Reinsnes, Mats Schjelderup (Høgskolen i Bodø, 2010)
Masteroppgave i Energy management - Høgskolen i Bodø, 2010